1996
DOI: 10.1002/(sici)1097-0142(19960215)77:4<710::aid-cncr17>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analyses of epidermal growth factor receptors, HER-2/neu oncoprotein and cathepsin D in nonmalignant and malignant uteri

Abstract: Determination of the frequency and levels of EGF receptors, HER-2/neu protein, and cathepsin D in uteri with and without cancer and the availability of reference materials developed in our laboratory, will allow evaluation of their prognostic value in cancers of the uterus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…These studies were performed on relatively small series, because only one group included more than 100 cases (Lšsch et al, 1996). In one study, Cat D levels were quantified by ELISA (Maudelonde et al, 1990), and in three (Nazeer et al, 1992;Scambia et al, 1995;Sanfilippo et al, 1996) by an immunoradiometric (IRMA) procedure similar to that used by us. In another article, Cat D was detected by immunohistochemistry (IHC) (Lšsch et al, 1996).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These studies were performed on relatively small series, because only one group included more than 100 cases (Lšsch et al, 1996). In one study, Cat D levels were quantified by ELISA (Maudelonde et al, 1990), and in three (Nazeer et al, 1992;Scambia et al, 1995;Sanfilippo et al, 1996) by an immunoradiometric (IRMA) procedure similar to that used by us. In another article, Cat D was detected by immunohistochemistry (IHC) (Lšsch et al, 1996).…”
Section: Discussionsupporting
confidence: 84%
“…Our data in endometrial cancer are similar to those published by Sanfilippo et al (1996) and higher than those reported by three other groups (Maudelonde et al, 1990;Nazeer et al, 1992;Scambia et al, 1995). The reasons underlying these divergent results are not clear because most of these authors used essentially the same methodology as that used by us.…”
Section: Discussionmentioning
confidence: 99%
“…Specific binding capacities of ER , PR , and epidermal growth factor receptor (EGFR) , and the level of human epidermal growth factor receptor‐2 (HER‐2/neu) oncoprotein were determined as described earlier. ER and PR measurements were performed by enzyme immunoassay (EIA) and/or ligand‐binding methods using standardized reagents in the presence of a reference specimen .…”
Section: Methodsmentioning
confidence: 99%
“…The concentration and distribution of cytosolic and nuclear receptors (ER, PgR) under steroid stimulation prove the extreme sensitivity to development fibrocystic change from exogenous steroids. Testosterone and its metabolites might be able to induce the secretion of mitogenic factors and stimulate the production of proteins such as cathepsin D and plasminogen activator, which may degrade the extracellular matrix and thereby accelerate the growth factors [18]. ER is an intracellular protein, but its exact localization is very controversial.…”
Section: Discussionmentioning
confidence: 99%